A revised landslide inventory of the Calabria Region (Italy) - Giuseppe Cianflone; Salvatore Larosa; Lisa Beccaro; Antonio Viscomi; Cristiano Tolomei; Giovanna Chiodo; Tiziana La Pietra; Sergio Leonetti; Luigi Mollica; Annamaria Pellegrino; Antonio Servidio; Salvatore Siviglia; et al. (Journal of Maps)
The Calabria region is prone to widespread landslides due to its unique geological and climatic conditions. Landslide risk is crucial for spatial planning, making an updated inventory essential. A revised landslide inventory for Calabria (CaLaI) was created by processing previous inventories and new mapping, supported by local field surveys and A-InSAR Sentinel-1 data. The results were compiled in an atlas with four maps, featuring 16913 landslides, categorized as follows: 8081 slides, 5166 diffuse instability areas, 2065 complex landslides, 965 flows, 352 areas affected by erosion, 234 falls/topples, and 50 deep-seated gravitational slope deformations. Of the total, 9253 are active, and 760 are dormant/suspended. Additionally, a WebGIS platform was developed for quick visualization and continuous updating of the landslide inventor.